Análisis de factores que inciden en la creación de pequeñas y medianas empresas de transformación en el cantón Guaranda, provincia Bolívar, período 2016-2017 - Suango Olmedo, Maryuri Estefania (2017)
With the purpose of knowing which are the most important factors that influence the creation of small and medium enterprises of transformation, the present investigation was carried out, taking as main focus the small and medium enterprises of the Canton Guaranda, and as baseline theories Which provide the necessary information for a better understanding and development of the subject, which requires a detailed study of each of the relevant aspects that contribute to the research. As support for conducting the research, the policies, regulations and norms that govern and control the creation of small and medium-sized processing enterprises are used, which are duly controlled by different governmental institutions to verify their correct functioning, and were used Techniques such as the survey and the deductive, analytical-synthetic, historical-comparative techniques necessary to complement the theoretical information obtained. Through the collection of data obtained (survey of small and medium enterprises registered in the database of the Ministry of Productivity MIPRO) through field research, it was identified that the most influential factors in the creation of a new company are The social ones in a primordial way, followed by the economic factors and the political, legal and regulatory factors, considering its importance and its vital application within the activities that are going to carry out each one of the companies. Matrixes were developed to establish the importance and impact of each of the internal and external factors, assigning them weight, impact level and influence in the creation of small and medium enterprises. The scope of this research is to determine the factors with greater influence to establish strategies of improvement that can be applied to obtain positive results, which are made known through applicable conclusions and recommendations as possible alternatives of solution to the problem found.